Netnografi Pesan Moral Dalam Vlog Atap Negeri Fiersa Besari - Agustian, Dimas Joni; SM, Anis Endang; Octaviani, Vethy Octaviani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The rapid development of information technology has encouraged the presence of social media which has influenced changes in people's lifestyles and communication patterns. One product of this technological development is YouTube. This research aims to find out the moral message in the Atap Negeri vlog on Fiersa Besari's Youtube in the video entitled "Gunung Patah-Bengkulu". This research is qualitative research using netnography methods. In this research, the author chose the 30 comments most frequently mentioned by netizens on comments pages. Then create coding which then produces 30 (thirty) abstractions which are then formed into 3 (three) categories by the author according to experts. The theory used in this research is computer mediated communication (CMC). The results of the research show that after watching this vlog video, many netizens' perspectives are directed in a positive direction because there are many moral messages that can be taken away which are expressed again by them through the comments page. There are several categories in this research, namely the category of human relationships with nature, the category of human relationships with themselves and the category of human relationships with other humans in the social environment. Netizens' comments in this category can be used as material to raise the enthusiasm of the national roofing team, especially for Fiersa Besari, so that they can create more quality climbing content and also serve as evaluation material for the local government to prevent poaching of protected animals and illegal cutting of trees.